A cross-sectional study on factors influencing attendance to eye screening - Mat Isa, Rif'atunnailah; Saidi, Sanisah; Salam, Adzura; Nurumal, Mohd. Said; Jamaludin, Thandar Soe Sumaiyah (Elsevier, 2021)
This study aimed to survey the factors influencing attendance to eye screening among Diabetes mellitus (DM) patients. This cross-sectional survey was carried out among 170 DM patients using self-administered questionnaires. Majority of participants, 45.9% (n = 78) highlighted that lack of information regarding diabetes and not understanding the significance of eye screening are the barriers to eye screening. Whereas, 10.6% (n = 18) reported lack of access to healthcare facilities, 6.5% (n = 11) experienced time limitation and 2.9% (n = 5) suffered financial issues. However, more than half of the participants (58.2%) have good knowledge related to diabetic eye complications. There was a significant difference between educational level with patients’ attendance in yearly eye screening. Lack of information received by the patients on the importance of eye screening and communication issues seems to be prominent and becomes the reason for patients not attending eye screening.